DevOps in Industry 4.0: A Systematic Mapping - Suescún-Monsalve, Elizabeth; Pardo-Calvache, César-Jesús; Rojas-Muñoz, Sergio-Andrés; Velásquez-Uribe, Alejandro (Revista Facultad de Ingeniería, 2021)
DevOps is the acronym for the integration of development and operations, which allows the improvement of communication and collaboration. Likewise, its objective is to help organizations develop software products and services quickly without sacrificing quality or cost. Additionally, its focus is on development, integration, delivery, release, testing, and continuous monitoring through the automation of tasks. Industry 4.0 solutions seek to digitize the industries’ processes and services to make them faster, safer, and more efficient through new technologies. These developments are not unrelated to the practices proposed by DevOps. This article presents a systematic mapping of the literature to identify the adoption prospects of DevOps practices for Industry 4.0 solutions reported in the literature. This work gathers proposals that show the importance and relevance of adopting DevOps to develop solutions for Industry 4.0. Organizations must prepare to address Industry 4.0 solutions; this will allow them to survive and prosper in the era of the Fourth Industrial Revolution. Therefore, it is necessary to conceptualize and adopt a solution development model that enables them to address these challenges and DevOps with its principles and standards, which would reduce operating costs and improve the service levels, efficiency, and administration of the different areas.